2017
DOI: 10.1186/s12894-017-0261-z
|View full text |Cite
|
Sign up to set email alerts
|

A gonadotropin-releasing hormone antagonist reduces serum adrenal androgen levels in prostate cancer patients

Abstract: BackgroundAdrenal androgens play an important role in the development of castration-resistant prostate cancer therapeutics. The effect of gonadotropin-releasing hormone (GnRH) antagonists on adrenal androgens has not been studied sufficiently. We measured testicular and adrenal androgen levels in patients treated with a GnRH antagonist.MethodsThis study included 47 patients with histologically proven prostate cancer. All of the patients were treated with the GnRH antagonist degarelix. The mean patient age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Moreover, degarelix overcomes the problems of first- and second-generation antagonists, such as short lasting efficacy and the induction of allergic reactions [ 16 , 18 , 19 ], becoming a popular option for medical castration. It has been reported that antagonists can not only achieve the suppression of testosterone secretion through the inhibition of the GnRH receptor, luteinizing hormone secretion and follicle-stimulating hormone secretion, but also significantly reduce the adrenal-derived androgen level in serum [ 20 ]. Intermittent treatment with degarelix can maintain the inhibition of PSA and improve sexual function as well as the quality of life [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, degarelix overcomes the problems of first- and second-generation antagonists, such as short lasting efficacy and the induction of allergic reactions [ 16 , 18 , 19 ], becoming a popular option for medical castration. It has been reported that antagonists can not only achieve the suppression of testosterone secretion through the inhibition of the GnRH receptor, luteinizing hormone secretion and follicle-stimulating hormone secretion, but also significantly reduce the adrenal-derived androgen level in serum [ 20 ]. Intermittent treatment with degarelix can maintain the inhibition of PSA and improve sexual function as well as the quality of life [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may be attributed to degarelix’s ability to also reduce serum adrenal androgen levels in patients with prostate cancer. 22 Furthermore, in the first 1–2 weeks of treatment, the median LH and FSH levels of patients in the leuprolide group increased due to the mechanism of action; however, median LH and FSH levels in the degarelix group declined more rapidly after the start of the treatment and remained suppressed until the end of the study. 8 At the end of the 12-month study, median FSH levels in the 240/80 mg degarelix, 240/160 mg degarelix and leuprolide groups decreased by 88.5%, 89.0% and 54.8%, respectively.…”
Section: Degarelixmentioning
confidence: 96%
“…In addition, serum adrenal androgens may decrease to a lesser extent following LHRH antagonists (Miyazawa et al 2017). Studies with orchiectomy or LHRH agonists suggest that DHEA does not change substantially following ADT (Xu et al 2002, Oka et al 2003.…”
Section: Changes In Androgens and Estrogens Following Androgen Deprivmentioning
confidence: 99%